TTV virome marks immune exhaustion, α7nAChR alteration, and mortality in elderly patients with severe COPD - Laura Vitiello; Stefania Proietti; Dolores Limongi; Carla Prezioso; Paola Checconi; Paola Fortugno; Marco Quaranta; Fabrizio Maggi; Guido Antonelli; Stefano Bonassi; Patrizia Russo (GeroScience, 2026)

Towards a validation of the standard and enzyme-linked comet assay: a retrospective variability analysis - Peter Møller; Carina Ladeira; Christina Ziemann; Siegfried Knasmueller; Miroslav Mišík; Henriqueta Louro; Maria João Silva; Ann Karin Olsen; Amaya Azqueta; Sabine A. S. Langie; Stefano Bonassi; Maria Dusinska; et al. (Archives of Toxicology, 2026)

Micronucleus assay in buccal and urothelial epithelial cells of wildland firefighters exposed to wildfire smoke - Filipa Esteves; Joana Madureira; Bela Barros; Sara Alves; Josiana Vaz; Marta Oliveira; Klara Slezakova; Adília Fernandes; Maria do Carmo Pereira; Simone Morais; Stefano Bonassi; João Paulo Teixeira; et al. (Journal of Hazardous Materials, 2025)

Impact of occupational exposure to wildfire events on systemic inflammatory biomarkers in Portuguese wildland firefighters - Filipa Esteves; Joana Madureira; Bela Barros; Sara Alves; Joana Pires; Sandra Martins; Marta Oliveira; Josiana Vaz; Klara Slezakova; Maria do Carmo Pereira; Adília Fernandes; Simone Morais; et al. (Environmental Research, 2025)

Lifestyle, environment and other major determinants of frailty in older adults: a population-based study from the UK Biobank - Ali Hemadeh; Carlota Lema-Arranz; Stefano Bonassi; Leonardo Buscarini; Francesco Infarinato; Paola Romano; Alessia Finti; Franco Marinozzi; Fabiano Bini; Natalia Fernández-Bertólez; João Paulo Teixeira; Laura Lorenzo-López; et al. (Biogerontology, 2025)
Frailty is a geriatric multidimensional syndrome characterized by a loss of physiologic reserves and disproportionate vulnerability to external stressors and associated with increased risk of multiple negative health outcomes. Since frailty can be prevented, controlled, and even reverted in its early stages, identifying the main factors involved in its development is crucial to implement preventive and/or restorative interventions. The aim of this study was to assess the impact of a broad range of parameters, including host factors, lifestyle, diet, and environmental and occupational conditions, on the development of frailty in later life. A cross-sectional study was conducted on 221,896 individuals aged 60 and over classified as non-frail (119,332, 53.8%), pre-frail (93,180, 42.0%), and frail (9384, 4.2%) according to the frailty phenotype. Using principal component analysis and machine learning to streamline the data, significant associations were found between frailty risk and air quality, diet, smoking, working conditions, and heavy alcohol consumption. Early-life factors, including breastfed as a baby and maternal smoking around birth, also emerged as predictors of frailty, which was further characterized by clinical indicators like polypharmacy, levels of C-reactive protein and other biomarkers of inflammageing. This study provided robust and original evidence on the association between a large battery of potential risk factors, from early to later stages of life, and the occurrence of frailty in older age. These results will contribute to the development of effective prevention strategies and facilitate the early detection of individuals at high risk of developing frailty.

Occupational exposure to wildland firefighting and its effects on systemic DNA damage - Filipa Esteves; Joana Madureira; Carla Costa; Joana Pires; Bela Barros; Sara Alves; Josiana Vaz; Marta Oliveira; Klara Slezakova; Adília Fernandes; Maria do Carmo Pereira; Simone Morais; et al. (International Journal of Hygiene and Environmental Health, 2025)

A Special Issue honoring Prof. Michael Fenech - Armen Nersesyan; Claudia Bolognesi; Stefano Bonassi; Siegfried Knasmueller (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2024)

Objectives and achievements of the HUMN project on its 26th anniversary - Michael Fenech; Nina Holland; Errol Zeiger; Peter Wushou Chang; Micheline Kirsch-Volders; Claudia Bolognesi; Helga Stopper; Lisbeth E. Knudsen; Siegfried Knasmueller; Armen Nersesyan; Philip Thomas; Varinderpal Dhillon; et al. (Mutation Research - Reviews in Mutation Research, 2024)

DNA damaging effects of occupational exposure to glass fibres. Response to Madl and Keeton paper - Marcello Ceppi; Bozena Smolkova; Verona Buocikova; Elise Rundén-Pran; Naouale El Yamani; Eleonora Marta Longhin; Sivakumar Murugadoss; Marta Staruchova; Magdalena Barancokova; Katarina Volkovova; Erika Halašová; Soterios Kyrtopoulos; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2024)

The buccal micronucleus cytome assay: New horizons for its implementation in human studies - Michael Fenech; Siegfried Knasmueller; Armen Nersesyan; Claudia Bolognesi; Georg Wultsch; Christian Schunck; Emanuela Volpi; Stefano Bonassi (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2024)

Occupational exposure to pesticides: DNA damage in horticulturist from Nativitas, Tlaxcala in Mexico - Juana Sánchez-Alarcón; Mirta Milić; Stefano Bonassi; Sandra Gómez-Arroyo; Josefina Cortés-Eslava; Ana Rosa Flores-Márquez; Rafael Alexander Valencia-Sánchez; Rafael Valencia-Quintana (Environmental Toxicology and Pharmacology, 2023)

Empirical relationship between chromosomal damage and airborne particulate matter: A systematic review and meta-analysis of studies in exposed populations - Francisco Carlos da Silva Junior; Leticya Pinto de Araújo; João Paulo de Mendonça Freitas; Nilmara de Oliveira Alves; Stefano Bonassi; Silvia Regina Batistuzzo de Medeiros (Mutation Research - Reviews in Mutation Research, 2023)

Genotoxic effects of occupational exposure to glass fibres - A human biomonitoring study - Marcello Ceppi; Bozena Smolkova; Marta Staruchova; Alena Kazimirova; Magdalena Barancokova; Katarina Volkovova; Andrew Collins; Anton Kocan; Zuzana Dzupinkova; Alexandra Horska; Verona Buocikova; Jana Tulinska; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

Association of inflammatory mediators with frailty status in older adults: results from a systematic review and meta-analysis - Diego Marcos-Pérez; María Sánchez-Flores; Stefania Proietti; Stefano Bonassi; Solange Costa; Joao Paulo Teixeira; Juan Fernández-Tajes; Eduardo Pásaro; Blanca Laffon; Vanessa Valdiglesias (GeroScience, 2020)

Correction to: Psychiatric disorders and SLC6A4 gene variants: possible effects on alcohol dependence and alzheimer’s disease - Marco Calabrò; Laura Mandelli; Concetta Crisafulli; Stefano Porcelli; Diego Albani; Antonis Politis; George N. Papadimitriou; Marco Di Nicola; Luigi Janiri; Roberto Colombo; Giovanni Martinotti; Antonello Bellomo; et al. (Molecular Biology Reports, 2020)

Psychiatric disorders and SLC6A4 gene variants: possible effects on alcohol dependence and alzheimer’s disease - Marco Calabrò; Laura Mandelli; Concetta Crisafulli; Stefano Porcelli; Diego Albani; Antonis Politis; George N. Papadimitriou; Marco Di Nicola; Luigi Janiri; Roberto Colombo; Giovanni Martinotti; Antonello Bellomo; et al. (Molecular Biology Reports, 2020)

A review of telomere length in sarcopenia and frailty - Maria Lorenzi; Stefano Bonassi; Teresa Lorenzi; Silvia Giovannini; Roberto Bernabei; Graziano Onder (Biogerontology, 2018)

Temporal trend, geographic distribution, and publication quality in asbestos research - Donatella Ugolini; Stefano Bonassi; Alfonso Cristaudo; Giacomo Leoncini; Giovanni Battista Ratto; Monica Neri (Environmental Science and Pollution Research, 2015)